Patient and Procedural Risk Factors for Increased Postoperative Pain After Cesarean Delivery Under Neuraxial Anesthesia: A Retrospective Study. Issue 3 (September 2021) - Mehdiratta, J.E.; Saab, R.; Chen, Z.; Li, Y.J.; Habib, A.S.
Abstract : ( Int J Obstet Anesth . 2020;44:60–67) Satisfactory postcesarean pain management is important for many reasons, including allowing early mobility to decrease thromboembolic risk, improved newborn care, and decreased risk for postpartum depression. There is still room for improvement in the management of postoperative pain in cesarean patients and a need to better understand individual variability. This study aimed to identify risk factors associated with increased postoperative pain following cesarean delivery (CD).